Ultrastructural study of the TG180 murine sarcoma cell invasion by Toxoplasma gondii: comparison between in vivo and in vitro cell cultures - Hugo Marcelo Ribeiro Barbosa; Marcos Silva; Eloisa Amália Vieira Ferro; José Roberto Mineo (Memorias do Instituto Oswaldo Cruz, 2000)
Infection of non-adherent TG180 murine sarcoma cells with Toxoplasma gondii was compared, at the ultrastructural level, in both in vivo and in vitro conditions. Suspensions of 3.0 x 10(6) TG180 cells infected in vitro with 1.0 x 10(6) parasites of the RH strain were harvested between the first and 6th day post-infection and processed for transmission electron microscopy. In vivo infection was made by intraperitoneal inoculation in mice of 1.0 x 10(6) TG180 cells, that were co-inoculated with a parasite suspension at the same cell concentration. Cells were harvested 10, 20, 30 min and 24, 48 h post-inoculation and processed for transmission electron microscopy at the same conditions of the in vitro culture. It was observed TG180 murine sarcoma cells with intense and equivalent intracellular parasitism in both conditions. Host cells with parasitophorous vacuoles containing up to 16 parasites, as well as parasites undergoing mitoses or presenting a bradyzoite-like morphology, were frequently seen in both culture methods.